PC1, a non-peptide PKR1-preferring antagonist, reduces pain behavior and spinal neuronal sensitization in neuropathic mice. (January 2015) - Guida, F.; Lattanzi, R.; Boccella, S.; Maftei, D.; Romano, R.; Marconi, V.; Balboni, G.; Salvadori, S.; Scafuro, M.A.; de Novellis, V.; Negri, L.; Maione, S.; et al.
Graphical abstract: Abstract: Peripheral neuropathy is characterized by abnormal pain responses triggered by the release of several mediators and neuronal hyperexcitability at the spinal cord level. Emerging evidence indicates that the enhanced activity of dorsal horn neurons requires communication with glia and microglia, cells that are physiologically involved in neuronal wellbeing. Prokineticins (PKs), which include PK1 and PK2, represent a novel family of chemokines characterized by a unique structural motif comprising five disulfide bonds. They are expressed in the peripheral and central nervous system. PKs bind two G protein coupled receptors, PKR1 and PKR2, and participate in the regulation of several biological processes, including pain sensation. This study aimed to investigate the anti-nociceptive effect of PC1, a non-peptide PKR1-preferring antagonist, in a mouse model of neuropathic pain. To do this, we assessed the activity of spinal cord nociceptive neurons as well as astrocyte and microglia phenotypes after repeated administration of PC1 in vivo. PC1 treatment strongly delayed the development of thermal hyperalgesia and tactile and mechanical allodynia. It also reduced spinal microglial and glial activation 8 days post injury in spared nerve injury (SNI) mice. Neuropathic mice showed an increased level of PK2 protein in the spinal cord, mostly in astrocytes. PC1 treatment completely reversed the increased responsiveness to mechanical stimuli, the decreased threshold of neuronal activation, and the increased spontaneous activity that were observed in nociceptive specific (NS) neurons of SNI mice.